2017
DOI: 10.3847/1538-4357/aa6843
|View full text |Cite
|
Sign up to set email alerts
|

New Spectral Evidence of an Unaccounted Component of the Near-infrared Extragalactic Background Light from the CIBER

Abstract: The Extragalactic Background Light (EBL) captures the total integrated emission from stars and galaxies throughout the cosmic history. The amplitude of the near-infrared EBL from space absolute photometry observations has been controversial and depends strongly on the modeling and subtraction of the Zodiacal light foreground. We report the first measurement of the diffuse background spectrum at 0.8-1.7 µm from the CIBER experiment. The observations were obtained with an absolute spectrometer over two flights i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
107
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 61 publications
9
107
1
Order By: Relevance
“…Presence of the bump leads to a characteristic dip in the observed γ-ray spectra of distant sources. We have shown that account of possible spectral feature in the EBL makes constraints on the EBL flux from the γ-ray measurements consistent with "minimal EBL" flux level reported by direct measurement experiments in the 1 micron wavelength range (Matsuura et al 2017).…”
Section: Introductionsupporting
confidence: 72%
“…Presence of the bump leads to a characteristic dip in the observed γ-ray spectra of distant sources. We have shown that account of possible spectral feature in the EBL makes constraints on the EBL flux from the γ-ray measurements consistent with "minimal EBL" flux level reported by direct measurement experiments in the 1 micron wavelength range (Matsuura et al 2017).…”
Section: Introductionsupporting
confidence: 72%
“…Matsumoto et al (2005), however, using their IRTS data have announced and Matsumoto et al (2015) repeated the claim for detection of an excess emission of up to 6 times as large as the IGL at λ = 1 − 2 µm. A large excess has also been found by Sano et al (2015) at 1.25 µm and by Matsuura et al (2017) at 1 − 1.7 µm. It has been poined out by e.g.…”
Section: Optical Ebl In Context Of Other Wavelengthsmentioning
confidence: 64%
“…While direct measurements of the EBL SED have been attempted, most recently by Matsuura et al (2017) and Zemcov et al (2017), correct subtraction of contaminating foregrounds is challenging, and the measurements tend to be limited by systematic uncertainties. Robust lower bounds on the EBL SED, on the other hand, have been generated by summing the light expected based on resolved galaxies.…”
Section: Introductionmentioning
confidence: 99%